BAHASA DAN KREATIVITAS: ANALISIS TINDAK TUTUR ILOKUSI DALAM MEME KAMUS KEKINIAN BAHASA INDONESIA - I Desak Ketut Titis Ary Laksanti (Balai Bahasa Sulawesi Tengah, 2019)
AbstractThis research is an effort to describe linguistic phenomena occur among Indonesian younger generation which constitute a productive users of any kind of social media. The emergence of Indonesian currents meme dictionary in various social media are becoming a place of the younger generation for creativity.The exploitation of linguistic aspects is inseperable from this phenomena. The research findings show that speech act found in the Indonesian currents meme dictionary are dominated by: 1) expressive speech acts are used for expressing anger, dissapointments, jealousy, admirations, and longing, 2) assertive speech acts are used for expressing complaint, denials, aggrements, and mocks, 3) directive speech act are used for expressing commands and request something to the interlocutors, and 4) questioning speech act are used for lip service and to assertings something from the interlocutors. All of the speech act maybe delivered directly or indirectly, literally or non-literally to the interlocutors. Those speech act are strongly influenced by 1) love relationship, 2) women characteristics, 3) degree of intimacy, and 4) the speaker’s way of beginning and ending the communications.